Assessment of the Role of Intraoperative Frozen Section in Guiding Surgical Staging for Endometrial Cancer. Issue 5 (1st June 2016) - Wang, Xiaoyuan; Li, Li; Cragun, Janiel M.; Chambers, Setsuko K.; Hatch, Kenneth D.; Zheng, Wenxin
Abstract : Objective: The aim of this study was to assess the role of intraoperative frozen section (FS) in guiding decision making for surgical staging of endometrioid endometrial cancer (EC). Methods: Medical records were collected retrospectively on 112 patients with endometrioid EC, who underwent total hysterectomy and bilateral salpingo-oophorectomy at the University of Arizona Medical Center from January 1, 2010, to December 31, 2014. Only patients with endometrioid adenocarcinoma, grade 1, less than 50% myometrial invasion, and tumor size less than 2 cm determined by intraoperative FS omitted lymphadenectomy; otherwise, surgical staging was performed with lymph node dissection. The FS results were compared with the permanent paraffin sections (PSs) to assess the diagnostic accuracy. Results: The concordance rate of different variables between FS and PS in EC was 100%, 89.3% (100/112), 97.3% (109/112), and 95.5% (107/112), respectively, with respecting to histological subtype, grade, myometrial invasion, and tumor size. Diagnostic accurate rate of combined risk factors deciding surgical staging at the time of FS was 95.5% (107/112), and the discordance rate of all risk factors considered between FS and PS was 4.5%, resulting 3 cases (2.7%) undertreated and 2 cases (1.8%) overtreated. Conclusions: Despite nonideal FS evaluation, intraoperative FS diagnosis for EC is highly reliable by providing guidance for the intraoperative decisions of surgical staging at our institution, and such guidelines may be referenced by the institutions with sufficient gynecologic pathology expertise.